Theory and method in the social sciences. - Rose, Arnold M. (Arnold Marshall), 1918-1968 (University of Minnesota Press, 1954)
Theory and Method in the Social Sciences was first published in 1954. Minnesota Archive Editions uses digital technology to make long-unavailable books once again accessible, and are published unaltered from the original University of Minnesota Press editions. A series of essays dealing with some previously neglected areas of theory and research in the social sciences make up this volume. The problems considered fall into the general categories of social theory, values in social research, the contributions of sociological theory to the other social sciences, methodological issues in sociology, and some specific techniques of sociological research. The chapter entitled "A Theory of Social Organization and Disorganization," published here for the first time, won for Dr. Rose the 1952 prize of the American Association for the Advancement of Science for essays in social science. Although addressed primarily to sociologists, the book offers material of interest and value to other social scientists, particularly economists, psychologists, political scientists, and students of law